The Prediction of Outcomes in Patients Admitted with Traumatic Brain Injury Using the Rotterdam Score - Bikram Shakya; Bidur KC (Journal of Nobel Medical College)
Background: Traumatic brain injury is a leading cause of mortality and disability worldwide, necessitating accurate tools for prognosis to guide treatment and improve patient outcomes. The Rotterdam computed tomography score, a widely utilized prognostic tool based on cranial computed tomography findings, assesses critical parameters such as basal cistern status, midline shift, and traumatic subarachnoid hemorrhage. This study aimed to evaluate the Rotterdam Score's effectiveness in predicting outcomes among traumatic brain injury patients.